Relaxation-weighted Na-23 magnetic resonance imaging maps regional patterns of abnormal sodium concentrations in amyotrophic lateral sclerosis - Mueller, Hans-Peter; Nagel, Armin Michael; Keidel, Franziska; Wunderlich, Arthur; Hubers, Annemarie; Gast, Lena; Ludolph, Albert C.; Beer, Meinrad; Kassubek, Jan (Therapeutic Advances in Chronic Disease, 2022)
Objectives: Multiparametric magnetic resonance imaging (MRI) is established as a technical instrument for the characterisation of patients with amyotrophic lateral sclerosis (ALS). The contribution of relaxation-weighted sodium ((NaR)-Na-23) MRI remains to be defined. The aim of this study is to apply (NaR)-Na-23 MRI to investigate brain sodium homeostasis and map potential alterations in patients with ALS as compared with healthy controls.
CRIS-Team WoS Importer:2022-07-29